2015
DOI: 10.1021/acssuschemeng.5b00722
|View full text |Cite
|
Sign up to set email alerts
|

Amaranthus spinosusLeaf Extract Mediated FeO Nanoparticles: Physicochemical Traits, Photocatalytic and Antioxidant Activity

Abstract: Iron oxide nanoparticles were synthesized using Amaranthus spinosus leaf aqueous extracts reducing from ferric chloride. A. spinosus leaf extract is a rich source of amaranthine and phenolic compounds with high antioxidant and these molecules were used as reducing agents. The operating parameters of nanoparticles synthesis were optimized. Physicochemical, optical, and magnetic properties of synthesized nanoparticles were characterized using analytical techniques. Results confirmed that A. spinosus leaf extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(53 citation statements)
references
References 47 publications
3
39
2
Order By: Relevance
“…These nanoparticles showed highest rate of bromothymol blue degradation in comparison to Fe-ethylenediaminetetraacetic acid (Fe-EDTA) and Fe-ethylenediamine-disuccinic acid (Fe-EDDS). In another study, Muthukumar and Matheswaran [90] obtained iron oxide nanoparticles using Amaranthus spinosus leaf aqueous extracts. These nanoparticles were spherical with rhombohedral phase structure, smaller in size with large surface, and less aggregation than those produced with sodium borohydride.…”
Section: Reviewmentioning
confidence: 99%
“…These nanoparticles showed highest rate of bromothymol blue degradation in comparison to Fe-ethylenediaminetetraacetic acid (Fe-EDTA) and Fe-ethylenediamine-disuccinic acid (Fe-EDDS). In another study, Muthukumar and Matheswaran [90] obtained iron oxide nanoparticles using Amaranthus spinosus leaf aqueous extracts. These nanoparticles were spherical with rhombohedral phase structure, smaller in size with large surface, and less aggregation than those produced with sodium borohydride.…”
Section: Reviewmentioning
confidence: 99%
“…Synthesis of magnetite nanoparticles that absorb at wavelengths corresponding to 294 nm and 233 nm has been reported [27,33]. The minor differences in the absorption maxima of the obtained wavelengths reported by various authors have been suggested to be due to the binding of the different biomolecules from the leaf extract to the surface of the nanoparticles, their aggregation state and valency [36,37]. Presence of another broad spectrum peak was visible at 428 nm.…”
Section: Resultsmentioning
confidence: 91%
“…These two peaks could be attributed to two different phases of synthesized IONPs. The broadness of the peaks may be associated to different sizes as well as agglomeration of the nanoparticles [36]. Results of FTIR analysis revealed formation of IONPs using Ocimum tenuiflorum leaf extract (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…As reported by Sherman and Waite [23], species based on iron oxides and hydroxides have four predominant regions of absorption: ligand to metal charge transfer (250-400 nm) along with contribution of Fe 3+ ligand eld transition (290-310 nm), pair excitation process (400-600 nm) of magnetically coupled Fe 3+ ions, and two strong absorption bands near 640 and 900 nm of ligand eld transitions of Fe 3+ cation in the octahedral environment. e peak found at 290 nm is related to the formation of iron oxide nanoparticles [24] mediated by complex polyphenols contained in the mortiño extract. Recently, these polyphenols induced the reduction of silver ions to metallic silver during the synthesis of the silvergraphene nanocomposite [22].…”
Section: Characterization Of Multicomponent Nanoparticlesmentioning
confidence: 99%